Exposure to 3-Nitropropionic Acid Mitochondrial Toxin Induces Tau Pathology in Tangle-Mouse Model and in Wild Type-Mice - Lahiani-Cohen, Inbal; Touloumi, Olga; Lagoudaki, Roza; Grigoriadis, Nikolaos; Rosenmann, Hanna (Frontiers in Cell and Developmental Biology, 2020)
Oxidative stress, particularly of mitochondrial origin, plays an important role in the pathogenesis of neurodegenerative disorders, including Alzheimer’s disease (AD) and other tauopathies. Controversies regarding the responses of tau phosphorylation state to various stimuli causing oxidative stress have been reported. Here we investigated the effect of 3-nitropropionic acid (3NP), a mitochondrial toxin which induces oxidative stress, on the tangle-pathology in our previously generated double mutant (E257T/P301S, DM) -Tau-tg mice and in WT-mice. We detected an increase in tangle pathology in the hippocampus and cortex of the DM-Tau-tg mice following exposure of the mice to the toxin, as well as generation of tangles in WT-mice. This increase was accompanied with alterations in the level of the glycogen synthase kinase  (GSK3), the kinase which phosphorylates the tau protein, and in the phosphorylation state of this kinase. A response of microglial cells was noticed. These results point to the involvement of mitochondrial dysfunction in the development of the tangle-pathology and may suggest that interfering with mitochondrial dysfunction may have an anti-tangle therapeutic potential.